2020
DOI: 10.1186/s12884-020-02867-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and aetiologies of postpartum pyrexia; a retrospective analysis in a tertiary health facility in the Littoral Region of Cameroon

Abstract: Background: Postpartum febrile morbidity is relatively common, occurring in approximately 5-7% of births. Differentiating between potentially serious and benign causes of postpartum pyrexia (PP) is fundamental in curbing the mortality rate from sinister causes such as sepsis. The paucity of data on PP in Cameroon makes it difficult to access its actual burden. This study was aimed at determining the prevalence, risk factors and aetiologies of PP at a tertiary hospital in Douala, Cameroon. Methods: This was a 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…Therefore, healthcare givers should ensure close monitoring of mothers’ body temperatures even several days after birth for the timely detection of fever and, thus, timely diagnosis of postnatal infections such as puerperal sepsis. This finding is in line with the findings of a study conducted in Cameroon, which stated that postnatal fever was more common in the first 3 postnatal days, excluding the first 24 h [ 33 ]. The same study also emphasized that the timing of the onset of fever is an important management strategy for healthcare providers for the timely management of postnatal infections and other complications.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, healthcare givers should ensure close monitoring of mothers’ body temperatures even several days after birth for the timely detection of fever and, thus, timely diagnosis of postnatal infections such as puerperal sepsis. This finding is in line with the findings of a study conducted in Cameroon, which stated that postnatal fever was more common in the first 3 postnatal days, excluding the first 24 h [ 33 ]. The same study also emphasized that the timing of the onset of fever is an important management strategy for healthcare providers for the timely management of postnatal infections and other complications.…”
Section: Discussionsupporting
confidence: 91%
“…Our data also showed that perineal tearing is more likely to occur in the DRA and VD group. Perineal tear was one of the risk factors identified for some diseases, and the question of whether DRA causes perineal tearing, or vice versa, is worth further study [25]. One possibility for the connection between vaginal delivery and perineal tearing could be the inward contraction of abdominal muscles, particularly uterine, during delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Có 27 trường hợp NTHS trong mẫu nghiên cứu có chuyển dạ kéo dài (chiếm tỷ lệ 67,5%), cao hơn nhóm không có chuyển dạ kéo dài (chiếm 32,5%) với p < 0,05. Ngunyi và cộng sự (2020) đã chỉ ra rằng, thời gian chuyển dạ kéo dài trên 18 giờ làm tăng khả năng mắc nhiễm trùng hậu sản với OR = 26,760 (95% CI, 9,081 -63,218) [12]. Kết quả từ nghiên cứu của chúng tôi so với nghiên cứu trên có sự tương đồng với việc chuyển dạ kéo dài làm tăng tỷ lệ NTHS.…”
Section: Nhiễm Trùng Hậu Sản Và Thời Gian Chuyển Dạunclassified